Efficacy of a Culturally Adapted Cognitive Behavioural Internet-delivered Treatment for Depression - Richards, Derek; Salamanca-Sanabria, Alicia; Timulak, Ladislav; Connell, Sarah; Mojica Perilla, Monica; Parra-Villa, Yamilena; Castro-Camacho, Leonidas (My University, 2020)
Background: Internet-delivered treatments for depressive symptoms have proved to be successful in high-income Western countries. There may be potential for implementing such treatments in low- and middle-income countries such as Colombia, where access to mental health services is limited. Objective: The objective of this study was to assess the efficacy of a culturally adapted cognitive behavioral internet-delivered treatment for college students with depressive symptoms in Colombia. Methods: This was a randomized controlled trial with a 3-month follow-up. The program comprised seven modules. A total of 214 Colombian college students were recruited. They were assessed and randomly assigned to either the treatment group (n=107) or a waiting list (WL) control group (n=107). Participants received weekly support from a trained supporter. The primary outcome was symptoms of depression, as measured by the Patient Health Questionnaire - 9, and the secondary outcomes were anxiety symptoms assessed by the Generalized Anxiety Disorder questionnaire - 7. Other measures, including satisfaction with treatment, were evaluated after 7 weeks. Results: Research attrition and treatment dropouts were high in this study. On average, 7.6 sessions were completed per user. The mean time spent on the program was 3 hours and 18 min. The linear mixed model (LMM) showed significant effects after treatment (t197.54=−5.189; P<.001) for the treatment group, and these effects were maintained at the 3-month follow-up (t39.62=4.668; P<.001). Within-group results for the treatment group yielded a large effect size post treatment (d=1.44; P<.001), and this was maintained at the 3-month follow-up (d=1.81; P<.001). In addition, the LMM showed significant differences between the groups (t197.54=−5.189; P<.001). The results showed a large effect size between the groups (d=0.91; P<.001). In the treatment group, 76.0% (16/107) achieved a reliable change, compared with 32.0% (17/107) in the WL control group. The difference between groups was statistically significant (X22=10.5; P=.001). Conclusions: This study was the first contribution to investigating the potential impact of a culturally adapted internet-delivered treatment on depressive symptoms for college students as compared with a WL control group in South America. Future research should focus on identifying variables associated both with premature dropout and treatment withdrawal at follow-up. Trial Registration: ClinicalTrials.gov NCT03062215; https://clinicaltrials.gov/ct2/show/NCT03062215
PUBLISHED
Keywords: Culture; Internet; Cognitive behavioural therapy; Depressive symptoms; Students; South America; Digital Engagement